2020
DOI: 10.3389/fphar.2020.581544
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Oxytocin Improves Spontaneous Behavior and Reduces Mechanical Hypersensitivity in a Rat Model of Postoperative Pain

Abstract: The first few days post-surgery, patients experience intense pain, hypersensitivity and consequently tend to have minor locomotor activity to avoid pain. Certainly, injury to peripheral tissues produces pain and increases sensitivity to painful (hyperalgesia) and non-painful (allodynia) stimuli. In this regard, preemptive pharmacological treatments to avoid or diminish pain after surgery are relevant. Recent data suggest that the neuropeptide oxytocin when given at spinal cord level could be a molecule with po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…In line with previous studies [ 26 ], we did not find any role of sex in the association of oxytocin and pain. Although in animal models, oxytocin has been shown to directly decrease pain signaling to the spinal cord [ 39 , 40 ], it has also been suggested to elicit stress-induced hyperalgesia [ 13 ]. Furthermore, our observation of stress as a moderator of endogenous oxytocin effects is consistent with a previous study showing that higher levels of plasma oxytocin were associated with fewer depressive symptoms and more sensitive maternal behavior among women who reported high levels of psychosocial stress [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous studies [ 26 ], we did not find any role of sex in the association of oxytocin and pain. Although in animal models, oxytocin has been shown to directly decrease pain signaling to the spinal cord [ 39 , 40 ], it has also been suggested to elicit stress-induced hyperalgesia [ 13 ]. Furthermore, our observation of stress as a moderator of endogenous oxytocin effects is consistent with a previous study showing that higher levels of plasma oxytocin were associated with fewer depressive symptoms and more sensitive maternal behavior among women who reported high levels of psychosocial stress [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is interesting to point out that our results suggest that this neuropeptide could act as a pre-emptive analgesic. These results agree with a previous report showing that intrathecal injection of this neuropeptide prevents the development of postsurgical nociception . Nevertheless, at this point, we do not know if the same mechanisms elicited to prevent the long-lasting nociception (i.e., allodynia) will be operative when the oxytocin is given as a curative treatment (when the allodynia is fully established).…”
Section: Results and Discussionmentioning
confidence: 99%
“…These results agree with a previous report showing that intrathecal injection of this neuropeptide prevents the development of postsurgical nociception. 20 Nevertheless, at this point, we do not know if the same mechanisms elicited to prevent the long-lasting nociception (i.e., allodynia) will be operative when the oxytocin is given as a curative treatment (when the allodynia is fully established). In any case, more experiments designed to tackle this question are necessary.…”
Section: T H Imentioning
confidence: 99%
“…One weakness of this study is that we did not analyze the interaction of oxytocinergic and opioidergic neuronal systems using animal pain models. Many studies have demonstrated that OT improves pain in several animal models [30,32,34,58]. In addition, some reports have shown that activation of the OT receptor upregulates preproenkephalin gene expression, which is the precursor for enkephalin, the endogenous ligand for MOR [59,60].…”
Section: Discussionmentioning
confidence: 99%